Filtering Erroneous Soundings from Multibeam Survey Data - Herlihy, Daniel R.; Stepka, Thomas N.; Rulon, Timothy D. (The International Hydrographic Review, 2018)
As part of its continuing efforts to improve data quality, the National Oceanic and Atmospheric Administration (NOAA) has recently implemented a "prefiltering" procedure designed to identify and remove erroneous or questionable soundings from multibeam sonar data collected in support of the United States Exclusive Economic Zone Bathymetric Mapping Programme. Since the start of the 1991 field season, a simple, yet effective, prefiltering algorithm has been incorporated into the standard post-processing software used aboard NOAA ships equipped with MicroVAX-based survey systems. In addition, the prefiltering routine is also being utilized as part of NOAA’s current effort to convert its archive of older PDP-11 multibeam surveys to standard full-resolution "beam" format. The sounding verification criteria employed by the prefiltering algorithm is discussed in detail and statistical results from the first season of its implementation are presented.